Contingent effect of reactor strategy on the relationship between budget-related behaviours and departmental performance. - Pey, Teck Chuang. (2008)
This project seeks to investigate the relationship between budget-related behaviours (BRB) and departmental performance, under the effect of a reactor strategy. The main objective is to find evidence of a relationship between BRBs and performance. Additionally, this research seeks to establish the similarities and differences in behaviour and performance for companies in general and those adopting the Reactor strategy. This study uses multivariate canonical analysis in its questionaire survey.